CRITICAL EVALUATION ON ELECTRICITY SUBSIDYTO THE STATE ELECTRICITY COMPANY (PT PLN) - Mahpud Sujai (Pusbindiklat - LIPI, 2011)
This research has objectives to explore the effect of electricity subsidy to the financial performance of The State Electricity Company (PT PLN) and to describe the proportion of electricity subsidy compared to the total government expenditure and total central government expenditure. The method of this research is literature review with qualitative approach by exploring information through secondary data collection. This research used a descriptive analysis to interpret the collected data. The result showed that on average 40 percent revenue of PT PLN was derived from government subsidy with the total more than Rp50 trillion on average each year for electricity subsidy. Based on this fact, this research recommends government to decrease the electricity subsidy and allocate them to increase people’s welfare.